THE HIDING GIANT: A CASE OF AN INCIDENTAL FUNCTIONING METASTATIC ADRENAL CARCINOMA - MA, Md Syazwan; Y, Yusniza (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION The majority of incidental adrenal tumours diagnosed by imaging are non-functioning and small in size. However, in this case, a follow through from a CT angiogram of lower limbs led to the findings of a giant functioning metastatic adrenal carcinoma. CASE A 59-year-old lady with hypertension and T2DM on insulin was admitted for seizure with hypoglycaemia and hypokalaemia secondary to poor oral intake due to Left Lower Limb Necrotising Fasciitis. A CT angiogram of the left lower limb found necrotic aortocaval lymph nodes. Upon follow up a month later, to rule out either TB or malignancy, a CT abdomen/pelvis was done and showed a huge heterogenous suprarenal mass (10 x 11.6 x 8.7 cm) with metastases to the lymph nodes and lungs. On examination, patient was cushingoid and generally weak. Hormonal screen suggests Cushing’s syndrome and hyperandrogenism. A further CT adrenal protocol supports the diagnosis of adrenocortical carcinoma with referrals made for surgical intervention in Putrajaya Hospital but patient died of Severe Hospital Acquired Pneumonia with Upper GI Bleeding before surgical review. CONCLUSION Even though her admission was protracted there was no early identification of Cushing syndrome until CT abdomen/pelvis was done. Therefore, clinical suspicion of cortisol hypersecretion is crucial once there is hypertension with hypokalaemia. Hyperandrogenism, is extremely rare in adrenal carcinoma. However, this patient exhibited raised DHEAS levels combined with increased testosterone which support a diagnosis of a malignant adrenocortical tumour. This patient did not receive any treatment for her cancer. Should she have survived, surgical resection would be suggested despite lacking data for its benefit in metastatic disease. However, there is evidence that adrenalectomy coupled with chemotherapy may provide better survival.